Analisis Butir Soal Asesmen Sumatif Semester Gasal Mata Pelajaran Bahasa Indonesia: Item Analysis of Summative Assessment Questions for the Spring Semester of Indonesian Language - Junedi Junedi; Linda Eka Pradita; Sri Wulandari (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research is based on the analysis of items that have never been done at SMA Negeri 1 Grabag, precisely in the Indonesian language subject. The purpose of this study is to describe the quality of the summative assessment items of the odd semester of Indonesian language subject class XI at SMA Negeri 1 Grabag in the 2024/2025 academic year based on the aspects of validity, reliability, difficulty index, differentiation index, and the effectiveness of the items. This research uses quantitative descriptive method with data analysis techniques assisted by SPSS Ver. 25 and Microsoft Excel for quantitative analysis. The data collection technique used a systematic sampling technique with a sample of 70 student answer sheets. The question items analyzed were in the form of multiple choice questions totaling 50 items. The results of the study showed that; 1) The quality of the questions based on the validity aspect is moderate, with 26 valid items and 24 invalid items. 2) The quality of the questions based on the reliability aspect is high with an r_11 value of 0.692. 3) The quality of questions based on the aspect of difficulty level is in the very easy category, with 9 very difficult items, 16 medium items, and 25 very easy items. 4) The quality of questions based on the aspect of differential power is weak, with 28 items with weak differential power, 15 items with sufficient differential power, 2 items with good differential power, and 5 items with very weak differential power. 5) The quality of questions based on the effectiveness of the exterminator is poor, with 37 items in the excellent category, 25 items in the good category, 28 items in the poor category, 92 items in the poor category, and 18 items in the very poor category. In terms of the five aspects studied, the quality of multiple choice questions of the summative assessment of the odd semester of Indonesian language subject class XI SMA Negeri 1 Grabag in the 2024/2025 academic year is classified as a poor question.